2011
DOI: 10.1016/j.hrthm.2010.11.034
|View full text |Cite
|
Sign up to set email alerts
|

A common SCN5A polymorphism modulates the biophysical defects of SCN5A mutations

Abstract: BACKGROUND-Defects in the cardiac sodium channel gene, SCN5A, can cause a broad spectrum of inherited arrhythmia syndromes. After genotyping of a proband who presented with syncope, the SCN5A mutant P2006A and the common polymorphism H558R were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 33 publications
(44 reference statements)
1
53
1
Order By: Relevance
“…A recent study suggested that the domain I-II linker might be involved in stabilizing the fast inactivation of Na V 1.5 channels. 20 A mutation affecting the same amino acid, R620C, has been reported in association with long-QT syndrome, yet no electrophysiological characterization was performed in that study. 17 Mutations affecting neighboring codons (G615E and L619F) have been reported in patients with BrS.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study suggested that the domain I-II linker might be involved in stabilizing the fast inactivation of Na V 1.5 channels. 20 A mutation affecting the same amino acid, R620C, has been reported in association with long-QT syndrome, yet no electrophysiological characterization was performed in that study. 17 Mutations affecting neighboring codons (G615E and L619F) have been reported in patients with BrS.…”
Section: Discussionmentioning
confidence: 97%
“…53 Only about 35% of BS patients have been determined to have a genetic cause and nearly 30% carry a mutation in SCN5A. Besides the known mutations in several genes (SCN5A, GPD1L, SCN1B, SCN2B, SCN3B, MOG1, RANGRF, SLMAP, KCNE3, KCNJ8, HCN4, KCNE5, KCND3, CACNA1C, CACNB2, CACNA2D1, SCN10A and TRPM4), 2,3 other factors also have an important role in the resulting phenotype such as additional variants 54 (compound heterozygous disease-associated polymorphisms in family A), 15,16,55 epigenetic mechanisms (DNA methylation, posttranslational modifications and RNA mechanisms) 56 and phenotype modulators (vagal tone, sex hormones and febrile status). 57 It is likely that these additional factors influence the precise phenotypic expression and are therefore responsible for phenotypic overlap 41 and variable expressivity or incomplete penetrance 58 as seen in these families.…”
Section: Discussionmentioning
confidence: 99%
“…These SCN5A polymorphisms are also present in 20% of the general population. 15,16 Consecutively, his three daughters (patient A2, A3 and A4) were screened for BS and both polymorphisms, regardless of the presence of the muscular channelopathy.…”
Section: First Case/index Familymentioning
confidence: 99%
See 1 more Smart Citation
“…85 H558R also has been suggested to affect gating characteristics of mutant channels and modulate sodium channel disease expressivity. 86,87 Clinically, the H558R variant also affects ECG parameters and symptoms in patients with BrS. 88 A combination of certain polymorphisms (haplotype) within the regulatory (promoter) region of SCN5A also has been shown to modulate cardiac conduction.…”
Section: Genetic Modifiers Of Disease Expressivity and Severitymentioning
confidence: 99%